Resilience-oriented modeling and co-optimization for coupled power and water distribution systems - Yang, Yesen (2023)
The interdependencies between the power distribution system (PDS) and water distribution system (WDS) are well-acknowledged in resilience analysis. Such interdependencies can hinder the post-disruption service restoration of both systems, and prolong the overall recovery process. Aimed at handling these issues, this paper proposes a resilience-oriented modeling and co-optimization method for coupled power and water (CPW) systems. The model integrates critical features of modern CPW systems, such as microgrids and distributed generations for power and water treatment plants, pumps, and tanks, for the water side. The interdependencies are extracted and formulated from mutual demand aspects. Further, a multiobjective optimization is presented to simultaneously reduce the loss of power load (LOPL) and loss of water load (LOWL). Finally, the method is tested on a coupled 33-bus power and 25-node water system and the result demonstrates the effectiveness of the proposed model and algorithm.